The dialectic of the relationship between political violence and the legitimacy of the regime - Researcher Haider Jawad Hassan; Professor Dr. Mona Jalal Awwad (The college of law and political science journal, 2023)
Through the study, we concluded that Political violence is the use of physical or moral force, or the threat of its use, in order to achieve political goals related to the form of the regime and its orientations, and its economic and social policies. The protection of public order against rioters and disturbances, or by political forces towards the political system, justified in the duty to fight against oppression and tyranny. It becomes legitimate when it is a reaction to another structural or structural violence practiced by the tyrannical or colonial authority, and culminates in the establishment of a legitimate regime